Network Tools Application Design Based on C# with Intrusion Detection Methods and Simple Network Management Protocol - Rino Rino; Elroy Maxenchio Teja (Komunitas Dosen Indonesia, 2021)
The problem faced within this topic still encountered slow network constraints, thus disrupting work activities, the method used in writing is the SNMP (Simple Network Management Protocol) method & Intrusion Detection and by using the bee colony method to run tools designed to facilitate the retrieval. of network device information data and control the network. The solution that can be offered is to make it easier for admins to monitor and control network traffic and limit client network bandwidth, so as to get results in the form of organized and controlled network traffic. Management of network became important as prevention needed to securing the network and managing them requires the method mentioned above to make sure that network can be used without any problem